(untitled) (World Bulletin of Physical Education and Sports Science, 2025)
The article discusses the basic laws of growth and development in children, the importance of taking into account age characteristics in increasing physical fitness. Heterochrony, acceleration, physiological indicators of growth stages, and the effect of physical exercise are analyzed in a secondary school setting.